2012
DOI: 10.1007/s11916-012-0259-x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury Pain: Mechanisms and Management

Abstract: Patients with spinal cord injury (SCI) may experience several types of chronic pain, including peripheral and central neuropathic pain, pain secondary to overuse, painful muscle spasms, and visceral pain. An accurate classification of the patient's pain is important for choosing the optimal treatment strategy. In particular, neuropathic pain appears to be persistent despite various treatment attempts. In recent years, we have gained increasing knowledge of SCI pain mechanisms from experimental models and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(133 citation statements)
references
References 87 publications
3
120
0
Order By: Relevance
“…This is not surprising, however, Table 3 Summary of other secondary efficacy outcomes because neuropathic pain due to SCI is often severe and difficult to treat. 21 Treatment-related AEs in this study were consistent with the known safety profile of pregabalin. However, somnolence occurred more frequently in this study (33%) and in the previous SCI study (41%) 14 than in trials of pregabalin for the treatment of diabetic peripheral neuropathy or postherpetic neuralgia (12%-16%).…”
supporting
confidence: 82%
“…This is not surprising, however, Table 3 Summary of other secondary efficacy outcomes because neuropathic pain due to SCI is often severe and difficult to treat. 21 Treatment-related AEs in this study were consistent with the known safety profile of pregabalin. However, somnolence occurred more frequently in this study (33%) and in the previous SCI study (41%) 14 than in trials of pregabalin for the treatment of diabetic peripheral neuropathy or postherpetic neuralgia (12%-16%).…”
supporting
confidence: 82%
“…Use of medications that are recommended or commonly used for the treatment of SCI-NeP 7,8,14 was substantial and consistent with other chronic pain populations; opioids and NSAIDs, nonsteroidal anti-inflammatory drugs; were the most frequently prescribed treatments. Polypharmacy with pain-related medications noted in our study is not surprising given the high observed prevalence of musculoskeletal pain conditions in study patients.…”
Section: Discussionsupporting
confidence: 52%
“…Percent exposure (proportions of patients) and magnitude of use (number of prescriptions) were evaluated for medication classes recommended for the treatment of SCI-NeP based on clinical evidence, 7,8,14 for medications commonly used to treat NeP and associated sequelae. The number of prescriptions, days of therapy and average daily costs of pregabalin were determined during the follow-up period.…”
Section: Measures and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This probably reflects both more pain after the SCL and the frequent advent of spasticity. 15 The same was probably the case for the increase in ATC group M (musculoskeletal system) medications. 16 The significant increase in ATC group C (cardiovascular system) may reflect the dysfunctional autonomic and cardiovascular regulation after the SCL.…”
Section: Discussionmentioning
confidence: 92%